Race and Marriage in the Labor Market: A Discrimination Correspondence Study in a Developing Country - Arceo-Gomez, Eva O.; Campos-Vazquez, Raymundo M. (American Economic Review, 2014)
In Mexico, as in most Latin American countries with indigenous populations, it is commonly believed that European phenotypes are preferred to mestizo or indigenous phenotypes. However, it is hard to test for such racial biases in the labor market using official statistics since race can only be inferred from native language. The experiment consisted on sending fictitious curriculums responding to job advertisements with randomized information of the applicants. The resumes included photographs representing three distinct phenotypes: Caucasian, mestizo, and indigenous. We find that indigenous looking females are discriminated against, but the effect is not present for males.